The clinical impact of PCR‐based point‐of‐care diagnostic in respiratory tract infections in children. Issue 5 (7th February 2020) - Reischl, Anna Theresa; Schreiner, Daniel; Poplawska, Krystyna; Kidszun, André; Zepp, Fred; Gröndahl, Britta; Gehring, Stephan
Abstract: Background: Children are commonly affected by respiratory tract infections. Based on clinical symptoms, laboratory evaluation, and imaging, the causative pathogen often cannot be delineated. Point‐of‐care‐testing systems that provide an opportunity for fast detection of common viruses and some bacteria can therefore influence treatment's options. We aimed to examine whether the Biofire® FilmArray® has an effect on antibiotic treatment, duration of antibiotic therapy, and length of hospital stay within a pediatric cohort. Methods: We included children who were admitted to inpatient treatment with an acute respiratory tract infection from 02/2017 to 04/2018 using the FA respiratory panel for pathogen detection. The study group data were compared to the retrospective data of children admitted from 02/2016 to 02/2017, using a proprietary multiplex RT‐PCR. Results: A total of 322 children of the study group and 464 children of the control group were analyzed for clinical symptoms, laboratory findings, antibiotic treatment, and length of hospital stay. There was no significant reduction ( P  < .05) of antibiotic treatment and length of hospital stay. CRP, prehospital antibiotic treatment, antibiotic treatment, past medical history, age, and further pathogen detection showed a significant impact on antibiotic therapy, duration of antibiotic treatment, and length of hospital stay. Conclusion: The use of the FA did not result in a significant reduction of antibiotic treatment or in length of hospital stay. Other parameters had a more significant impact. Therefore, we suggest that standard operation procedures with therapy guidelines are necessary to provide an effective application of POCT systems.